Exploring The Role Of Intelligent Facades In Enhancing Energy Efficiency In Educational Buildings: A Scoping Review - Samar Abu Samaan; Madihah Mat Idris (Semarak Ilmu Publishing, 2026)
Non-Indexed Publication